MELANOMA STAGING (TNM SYSTEM) AND PROGNOSTIC FACTORS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The process of figuring out how far a cancer has spread and where it is in the body is known as cancer staging. In addition to offering the most precise prognostic estimate, a comprehensive staging is essential since the tumor's stage affects a number of critical decisions, including therapy selection and follow-up tactics. The American Joint Committee on Cancer (AJCC) published the eighth version of the TNM classification in 2017, which serves as the foundation for the current melanoma staging system. There are five stages (0–IV) in both the clinical and pathological staging. The Breslow thickness, the pathological presence or absence of ulceration in the primary tumor, the number and presence of tumor-involved regional lymph nodes, the presence or absence of in-transit, satellite, and/or microsatellite metastases, and the presence of distant metastases are some of the factors that determine the stage of a melanoma. An appropriate medical workup in accordance with the stage and physical examination should be carried out after a melanoma diagnosis. In order to identify a possible recurrence or a second primary melanoma, ongoing patient monitoring is essential and should last a lifetime. Different follow-up plans have been proposed, but there is currently no widely accepted follow-up strategy program. With the rising usage of innovative current medicines (immunotherapies and targeted therapies), future prospective studies are required to assess various follow-up methods based on the chosen therapy.